Peluang Dan Tantangan Lembaga Keuangan Mikro Syariah (BMT) Dalam Mengurangi Kemiskinan Di Nusa Tenggara Barat - Suriadi, Irwan (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
The objectives of this study were (a) to analyze the opportunities and challenges of Islamic microfinance institutions (BMT) in West Nusa Tenggara (b) to analyze the development strategy of Islamic microfinance institutions (BMT) in West Nusa Tenggara. The type of this research is descriptive research. The analysis technique used in this research is SWOT Analysis (Strength, Weakness, Opportunity, Treath). The results showed that the supporting factors can be seen from the strengths and opportunities of Islamic microfinance institutions (BMT) in West Nusa Tenggara that must have a strategic location and community empowerment by Islamic microfinance institutions (BMT), the inhibiting factor can be seen from the weaknesses and threats posed by Islamic microfinance institutions (BMTs) in West Nusa Tenggara, namely the lack of socialization from Islamic banks working on micro markets, the policy strategy of Islamic microfinance institutions (BMT) in the face of threats, namely Islamic microfinance institutions (BMT) in Nusa Tenggara The West must continuously develop itself creatively, innovatively and always have improvements in service to customers of Islamic microfinance institutions (BMT)